CORELATION BETWEEN RHEUMATIC DISEASE AND AUTOHEMOLITIC ANEMIA - Spasovski, Dejan; Sandevska, Emilija; Balkanov, Svetlana Krsrevska; Veljanovska, Aleksandra Pivkova (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
The autoimmune hemolytic anemias antibody can be hot or cold, have an incidence of 70 to 80% may be idiopathic in 50 to 60% and the rest of the cases secondary to lymphoproliferative disorders, collagen disease, drugs, solid tumors, infections and inflammatory bowel disease. RA may result in the reduced lifespan of red blood cells. This could lead to anemia if the body is unable to produce new red blood cells at a sufficient rate. Understanding these links between RA and anemia is crucial. Anemia is a common comorbidity in individuals with rheumatoid arthritis (RA). In fact, anemia of the type characterized by low serum iron concentrations in conjunction with adequate iron stores is frequently associated with RA and has served as a model for anemia of chronic disease. Rheumatoid vasculitis can affect blood vessels in many parts of your body. For this reason, it can cause many different symptoms. It most often damages blood vessels to the skin, fingers and toes, nerves, eyes, and heart. This reduces blood flow to these areas and damages them. Rheumatoid arthritis (RA) may be associated with a range of extraarticular manifestations, with hematologic complications including anemia and other conditions with hematologic abnormalities, such as Felty syndrome and lymphoproliferative disorders, particularly lymphoma and large granular lymphocyte (LGL) leukemia Keywords : rheumathic disease, autohemolitic anemia.